Functional Aspect of Studying the Translation of Phonographic Stylizations - Статівка, Анна Олександрівна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2018)
The article deals with the specifics of translating phonetic stylizations (PhS) as the important stylistic means of the character’s characterization in the aspect of their functionality. Functional characteristics of such PhS as imitations of speech specifics of a person caused by his / her social / territorial status, foreign origin, as well as physical / emotional state are considered as those having a considerable impact on the selection of the strategies and methods of translation. The main functions of PhS were determined as follows: characterological – PhS as a means of conveying individual speech traits; emotive – PhS as a means of revealing psychological states of a person, and expressive – PhS as a means of de-automatization of information perception by a reader and attraction of his / her attention. The main strategies of rendering functions of PhS in the English-Ukrainian translation were exposed and described. The results of the research demonstrate that striving to render the functions of PhS translators more often use parallel means in the target language. They seek to achieve fluency and naturalness within the strategy of domestication. The violation of the original functionality is seen as the communicative failure of the translator.